Communication—Proving the Importance of Pt-Interlayer Position in PEMWE Membranes for the Effective Reduction of the Anodic Hydrogen Content. Issue 9 (24th September 2021) - Martin, Agate; Abbas, Dunia; Trinke, Patrick; Böhm, Thomas; Bierling, Markus; Bensmann, Boris; Thiele, Simon; Hanke-Rauschenbach, Richard
Abstract : Gas crossover through the membrane poses a significant challenge to proton exchange membrane water electrolysers. This work investigates the influence of the position of platinum-based recombination interlayers integrated in the membrane on the anodic hydrogen in oxygen content. The results show that all interlayer positions reduce the anodic hydrogen content without performance losses compared to the reference without interlayer. However, an interlayer positioned closer to the anode is more effective than closer to the cathode. Further, the effect of the interlayer is more pronounced with increasing anode pressure.